PARTISIPASI POKDARWIS DAN MASYARAKAT DALAM PENGEMBANGAN PARIWISATA SERTA DAMPAK EKONOMI YANG DIRASAKAN OLEH MASYARAKAT DI DESA WISATA SUMBERBULU DESA PENDEM KECAMATAN MOJOGEDANG KABUPATEN KARANGANYAR - Azhari, Shafira Intan; Suhita, Damayanti (Solidaritas, 2025)
The purpose of this study was to determine the form of participation carried out by POKDARWIS and also the community in developing tourism and the economic impacts arising from tourism activities felt by local residents in the Sumberbulu tourist village, Mojogejang District, Karanganyar Regency. This study is classified into descriptive research with a qualitative approach. The sample of data sources or informants was determined by purposive sampling. The informants selected were the head of the management or head of POKDARWIS, homestay owners and residents of Sumberbulu village. Data collection techniques used observation and interviews. Observation was used by the author to obtain data on the level of community participation. Interviews were used by the author to determine the community empowerment strategy in the development of the Sumberbulu tourist village. This study uses the Participation theory by Aprelia Theresia (2014) which uses four indicators in its theory. The participation indicators used as guidelines in this study are participation in decision making, participation in activities, participation in monitoring and evaluation, participation in utilization of results. From the four indicators used it can be concluded that residents in the Sumberbulu tourist village are involved in various tourism activities starting from participation in decision making even though in its implementation the final decision is taken by POKDARWIS, in participation in community activities and POKDARWIS actively contribute to the management of facilities and implementation of tourism programs, participation in monitoring and evaluation in this participation the community is not included in the routine evaluation carried out by POKDARWIS, participation in utilization of results in this participation shows that the tourism village program has had a positive impact on the economy and social life of the community.